Climatology of summer Shamal wind in the Middle East. Issue 1 (5th January 2016) - Yu, Yan; Notaro, Michael; Kalashnikova, Olga V.; Garay, Michael J.
Abstract: The Middle Eastern Shamal is a strong north‐northwesterly wind, capable of lifting dust from the Tigris‐Euphrates basin and transporting it to the Persian Gulf and Arabian Peninsula. The present study explores the poorly understood spatial and temporal variability of summer Shamal on the diurnal, seasonal, and interannual time scales, along with its influence on dust storm activity and sensitivity to global patterns of sea surface temperature using a comprehensive set of observational data. Statistics of the summer Shamal season are quantified for the first time, including its onset, termination, duration, and the occurrence of distinct break periods. Based on a multistation criteria, the mean onset and termination of the Shamal season occur on 30 May ± 16 days (1 standard deviation) and 16 August ± 22 days, respectively. Anomalously early (late) onset and termination of the Shamal season are typically associated with La Niña (El Niño) conditions, which favor (inhibit) the development of the Iranian heat low in spring and inhibit (favor) its persistence into late summer. Dust source regions in the Tigris‐Euphrates basin and Kuwait, as well as southeastward dust transport during the summer Shamal, which cannot be detected by satellite aerosol products alone, are identified, for the first time, from the Multiangle Imaging Spectroradiometer plume motion vector products and confirmed by surface observations and lidar data. A close interrelationship has been revealed among summertime dust activity across the eastern Arabian Peninsula, frequency of Shamal days, and duration of the Shamal season on the interannual time scales. Key Points: Middle Eastern summer Shamal causes increased occurrence of dust storms Summer Shamal behaves like summer monsoon with variability in onset and termination Early (late) onset and termination are typically supported by La Niña (El Niño)